Assessing affordability as water poverty in Metropolitan Barcelona. Issue 11 (2nd November 2021) - Yoon, Hyerim; Domene, Elena; Sauri, David
ABSTRACT: Water poverty is a multidimensional concept open to a variety of definitions. In this paper, we focus on the affordability component of water poverty which emerges as the most relevant dimension of water poverty in the developed world where an increasing number of households are unable to afford the price of water. As in energy poverty, this degrades the metabolic flows of an essential resource in households threatening the livelihoods of members. We examine water affordability in the Metropolitan Area of Barcelona combining quantitative and qualitative information. Using data from Metropolitan Surveys as well as from specific studies, we depart from quantitative assessments of the impact of water affordability for the subgroup of households defined as "at risk of poverty". We complement the quantitative analysis with data on arrears, accumulated debt, and water disconnections, among other variables. Qualitative analyses are drawn from interviews with affected people attending meetings of a social platform, APE, created to fight energy and water poverty, offer a more precise assessment of the impacts of water poverty in vulnerable households and of the coping strategies by the affected and by APE. While some important achievements must be noticed, especially the Catalan law prohibiting disconnections of essential services to vulnerable households as well as the provision of financial help to pay the bills, important problems remain, above all the accumulated debt and the special case of the growing number of families occupying empty flats with no water connections.